Gender Roles and the Gender Expectations Gap - Francesco D'Acunto; Ulrike M. Malmendier; Michael Weber; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2020)
Expectations about macro-finance variables, such as inflation, vary significantly across genders, even within the same household. We conjecture that traditional gender roles expose women and men to different economic signals in their daily lives, which in turn produce systematic variation in expectations. Using unique data on the contributions of men and women to household grocery chores, their resulting exposure to price signals, and their inflation expectations, we show that the gender expectations gap is tightly linked to participation in grocery shopping. We also document a gender gap in other economic expectations and discuss how it might affect economic choices.
Keywords: C90; D14; D84; E31; E52; G11; 330; gender gap; expectations; perceptions; experiences; exposure